Impact of RDG Location on IDMT Overcurrent Relay Operation and Coordination in MV Distribution System - Mohamed ZELLAGUI; Abdelaziz CHAGHI (Institute of Advanced Engineering and Science, 2014)
In recent years there has been an intensive effort to increase the participation of renewable sources of electricity in the fuel and energy balance of many countries. In particular, this relates to the power of wind farms attached to the power system at both the distribution network. However, in the presence of Renewable Dispersed Generation, (RDG) some problems in coordination of protection devices will occur, due to changes in fault current levels at different points. By installing RDG in power distribution networks, the fault current levels are changed and may lead to some miscoordination in IDMT Directional Over-Current Relay (DOCR). In this paper, a novel approach is presented to study the impact of RDG location (dRDG) on IDMT characteristic curve of relay, fault current (IF), operation time (T) for DOCR, and coordination time interval (CTI) between backup and primary relays and short circuit level index (ISC) in the presence there phase fault on medium voltage (MV) distribution network. This new approach has been implemented on the Algerian 10 kV distribution power system in Constantine.